DECISION SUPPORT SYSTEM FOR HELP RECIPIENTS HOPE FAMILY PROGRAM ON VILLAGE WARU WITH SAW METHOD - Siti Nurlela; Tuti Kurniawati; Siti Masturoh; Widiastuti Widiastuti; Ade Suryadi (Jurnal Techno Nusa Mandiri, 2020)
Waru Village is one of the villages in the Bogor Regency area. However, the selection of recipients of the Hope Family Program (PKH) in Waru Village is still subjective/qualitative so that the process of receiving the Hope Family Program (PKH) in Waru Village is not accurate and has not been on target. This makes the need for a method that can manage data on recipients of the Hope Family Program (PKH) and produce a ranking from the calculation of weight for the selection of recipients of the Hope Family Program (PKH). In making decisions about recipients of the Hope Family Program (PKH), there is a Simple Additive Weighting (SAW) method that can be used in quantitative problem-solving. With the SAW method, each criterion is compared with one another to provide results of recipients of the Hope Family Program (PKH) and provide an assessment of each recipient (alternative) of the Hope Family Program (PKH) in Waru Village. This study aims to determine the recipients of the PKH assistance program so that it can produce a decision on recipients of PKH assistance that the government distributes to the Waru village accurately on target.